Reversible oxidative addition of nonactivated C-H bonds to structurally constrained phosphenium ions - Roth, Daniel; Radosevich, Alexander T.; Greb, Lutz (Journal of the American Chemical Society, 2023)
A series of structurally constrained phosphenium ions based on pyridinylmethylamidophenolate scaffolds are shown to undergo P(III)/P(V) oxidative addition with C-H bonds of alkynes, alkenes, and arenes. Nonactivated substrates such as benzene, toluene, and deactivated chlorobenzene are phosphorylated in quantitative yields. Computational and spectroscopic studies suggest a low-barrier isomerization from a bent to a T-shaped isomer that initiates a phosphorus-ligand-cooperative pathway and subsequent ring-chain tautomerism. Remarkably, C-H bond activations occur reversibly, allowing for reductive elimination back to P(III) at elevated temperatures or the exchange with other substrates.
Gesehen am 29.11.2023